The Potentially Therapeutic Role of EPAC in Curbing the Process of Idiopathic Pulmonary Fibrosis via Differential Cellular Pathways - Cao X; Li Y; Shi J; Tang H (Dove Medical Press, 2021)
Xinwei Cao,1 Yajun Li,1 Jianrong Shi,2 Huifang Tang1 1Department of Pharmacology, School of Basic Medical Sciences, Zhejiang University, Hangzhou, 310058, People’s Republic of China; 2Department of Clinical Laboratory, Children’s Hospital, Zhejiang University School of Medicine, National Clinical Research Center For Child Health, Hangzhou, 310003, People’s Republic of ChinaCorrespondence: Jianrong ShiDepartment of Clinical Laboratory, Children’s Hospital, Zhejiang University School of Medicine, National Clinical Research Center For Child Health, Hangzhou, People’s Republic of ChinaEmail shijr999@hotmail.comHuifang TangDepartment of Pharmacology, School of Basic Medical Sciences, Zhejiang University, Hangzhou, People’s Republic of ChinaEmail tanghuifang@zju.edu.cnAbstract: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive fibrosis disease caused by genetic susceptibility (causative) and other indirect risk factors such as smoking, micro-aspiration and air pollution. Repeated damage of lung epithelial cells can cause fibroblast activation and excessive collagen will lead the scar formation and severe fibrosis. It has been decades since drugs for the treatment of IPF were developed, but clinical choices were limited. Exchange Protein directly Activated by cAMP (EPAC), as a newly emerging cAMP (adenosine 3ʹ,5ʹ-cyclic monophosphate) downstream molecule, plays a vital role in the cellular pathways of IPF such as inhibiting fibroblast proliferation, stress fiber formation and epithelium cell adhesion, so it may be a novel target for drug development and treatment for curbing IPF. Here, we hypothesize that EPAC may participate in the signaling pathways related to IPF in different cell types (fibroblasts; airway smooth muscle cells; vascular endothelial cells; lung epithelial cells; macrophages; mesenchymal stem cells; T cells), thereby playing a potentially therapeutic role in resisting the process of fibrosis. We summarize the current correlation between EPAC and IPF in these different cell types, and further insights into EPAC will help to optimize the pharmacological treatment for IPF.Keywords: EPAC, idiopathic pulmonary fibrosis, fibroblasts, cell types, cAMP, PKA